Stylalgia: a novel approach to treatment (Bangladesh Journal of Otorhinolaryngology, 2012)
Purpose:(1) To evaluate digital fracture of enlarged styloid as a clinical maneuver, in office setting, in relieving symptoms in stylalgia. (2) To avoid surgery or long term medications as definitive treatment of stylalgia. (3) To reduce the investigations, workload in OPD and thereby ultimately cutting the cost of health care.Methods: This study started with total relief of symptoms in a stylalgia patient instantaneously after incidental fracture of enlarged styloid process of the same side during routine clinical palpation. Encouraged with this we started this study; within the period from June 2008 to May 2010 total 36 patients were included in this study.Results: We had 36 cases with stylalgia, among them 4 cases had enlarged styloid so thick that they were resistant to digital fracture. Those 4 cases were taken for surgery. Among those four cases 3 (75%) were male. We found male styloid tougher and harder than that of females. We were able to fracture enlarged and symptomatic styloid in OPD in 32 cases. Among them after initial 1 hour, observation after the maneuver, 10 (31%) had complete of their symptoms and also 13 (40.6%) cases had considerable improvement of their symptoms within 1 hour, but 9 cases felt no improvement. We followed up our patients after, 1 week, 2 week, 1 month and 6 months. After 1 month, 26 had complete symptoms relief, 3 had considerable improvement and 3 felt no improvement. But after 6 months of follow-up, 2 cases with symptoms relieved completely, developed symptoms but with much lesser intensity.Conclusion: Using this simple in office procedure we were able to avoid long term medicines, recurrent investigations. By giving relief we could avoid surgeries in large majority of cases, making the already over burdened theater available to other patients and also cutting preoperative investigations. Thus we can cut the burden of health care for such chronic cases DOI:http://dx.doi.org/10.3329/bjo.v18i2.11990 Bangladesh J Otorhinolaryngol 2012; 18(2): 133-137